EVOLUTION OF NORMATIVE OF REQUIRED RESERVES OF THE CENTRAL BANK OF THE RUSSIAN FEDERATION - A. Savtsova; O. Kabanova; D. Telichko; N. Reveguk (Вестник Северо-Кавказского федерального университета, 2022)
In the article emphasize the importance of the study of mandatory reserves, both for commercial banks and for the economy of the country as a whole. The article deals with the concept of the policy of mandatory reserves, the legislative framework governing the policy of mandatory reserves in the Russian Federation, the types of policy of mandatory reservation. The analysis of changes in the norms of mandatory reserve requirements in Russia is carried out and the cause-and-effect relationship is revealed. It is concluded that the size of the required reserves will depend on macroeconomic indicators such as the liquidity of the banking sector and the supply of money in the country.